Production activities of food industry enterprises in besieged Leningrad (1941-1943) - Gribacheva, Anastasiya Pavlovna (Genesis: исторические исследования, 2025)
The relevance of this article is due to scientific interest in the study of the production process at food industry enterprises in besieged Leningrad. However, a number of issues within the framework of the above scientific problem still remain poorly understood and need to be developed by modern researchers. The industrial activities of food enterprises were aimed at producing goods for the needs of the city and the front. Plants, factories and combines restructured the organization of their work in the current new environment. In conditions of limited resources, the production process was accompanied by the search for the necessary raw materials and substitutes. They began to use soybeans, cakes, and soybean meal in their work, which is why the food range they produced was able to expand. The article uses the following research methods: historical, historical-genetic, logical and historical-systemic, through which it is possible to consider the production activities of Leningrad food enterprises as an integral system. The scientific novelty lies in the analysis of archival documentary sources, which made it possible to identify information about production work at food enterprises. The materials contain explanatory notes, reports on economic activities, orders, some of which are being introduced into scientific circulation for the first time. The documents preserved data on production plans, product quality, equipment characteristics, etc. Being in the most difficult blockade conditions, the factories continued to produce food products. After the winter of 1941-1942. the work process gradually began to recover. Some mothballed enterprises became productive from the beginning of 1942. New methods of manufacturing products were mastered in laboratories, which were then introduced into production. However, it was not possible to completely restore production operations.